Analisis Unsur Intrinsik Roman “Emil und die Detektive” Karya Erich Kästner - Devi Eka Purba; Mantasiah Mantasiah (Phonologie : Journal of Language and Literature, 2023)
Abstract. This study aims to describe the intrinsic elements in the form of characters, setting, plot, point of view, theme, and moral value in the novel "Emil und die Detective" by Erich Kästner.  The research data is in the form of primary data and secondary data.  Primary data is direct data from the text of the novel “Emil und die Detective”.  Secondary data is supporting data that contains additional information in the form of journals, articles and books.  Data were analyzed based on a qualitative approach with content analysis.  The results of the research are as follows, setting of place: Berlin, setting of time: summer vacation, social environment: culture, plot: progressive plot, theme: adventure, point of view: third person omniscient, moral value: doesn’t easily trust strangers strangers.  Character education values: religious values, integrity values, independent values, and mutual cooperation values.Keyword: intrinsic element, content analysis, Emil und die Detektive, Erich Kästner